Sexual differences in the clinical features of antipsychotic-induced hyperprolactinemia in patients with schizophrenia - E. G. Kornetova; V. V. Tiguntsev; A. N. Kornetov; A. A. Goncharova; O. A. Lobacheva; A. A. Davydov; S. A. Khardikova; S. A. Ivanova; A. V. Semke (Бюллетень сибирской медицины, 2019)
The goal was to identify gender differences in the clinical features of antipsychotic-induced hyperprolactinemia in patients with schizophrenia.Materials and methods. 98 patients from the Department of Endogenous Disorders of the Research Institute of Mental Health Clinic in Tomsk were examined. Persons aged 18–50 were included with followup treatment for at least 1 year, whose condition corresponded to the ICD-10 schizophrenia criteria. Prolactin levels were determined by ELISA using the PRL Test System reagent kit (MonobindInc., USA). The base map of sociodemographic and clinical-dynamic features for patients with schizophrenia was used. Statistical processing of data was performed using the Statistica 12.0 software package. Mann–Whitney U test, Pearson’s χ² criterion, including Yates correction, and Fisher’s two-sided test were used for comparing small samples.Results. The average serum concentration of prolactin in women was 52.4 ± 39.1 ng/ml, in men it was 26.7 ± 19.7 ng/ml. Hyperprolactinemia was detected in 23 (47.9%) women and 25 (50%) men. Among women with hyperprolactinemia, statistically significant “Weight Gain” and “Headache” parameters were more common (p = 0.044 and p = 0.005, respectively). Men with hyperprolactinemia had higher BMI rates (p = 0.0066). For the rest of the UKU paragraphs, no significant differences were found in both men and women. Men presented fewer complaints and were less willing to discuss sexual dysfunction.Conclusion. Antipsychotic-induced hyperprolactinemia in patients with schizophrenia does not always have a full range of specific clinical manifestations and needs careful examination of patients with account of gender characteristics, as well as regular monitoring of the prolactin level in the serum of patients.